A case of an elderly female who developed subacute pleuropericarditis following BNT162b2 mRNA COVID-19 vaccination. Issue 3 (September 2022) - Mizoguchi, Tatsuya; Yokoi, Masashi; Shintani, Yasuhiro; Yamamoto, Junki; Mori, Kento; Fujita, Hiroshi; Ito, Tsuyoshi; Sugiura, Tomonori; Seo, Yoshihiro
Abstract: Despite the established safety of BNT162b2 coronavirus disease 2019 (COVID-19) vaccine, some rare but serious complications have been previously reported. Here, we report a rare case of an elderly female who developed subacute pleuropericarditis after the vaccination. An 88-year-old female experienced weight gain and dyspnea three days after the second dose of BNT162b2 vaccination, and one month later, presented to our hospital due to the exacerbation of the symptoms. Computed tomography showed remarkable pericardial and bilateral pleural effusions, and transthoracic echocardiogram visualized collapse signs of right and left atrium which indicates pre-tamponade. Percutaneous drainages of pericardial and pleural effusions stabilized her vital condition and revealed that all of them were exudative, indicating the presence of pleuropericarditis. Finally, we diagnosed this case as COVID-19 vaccine-associated pleuropericarditis because there were no signs of bacterial/viral infection or any other relevant causes except for the vaccination. When the pericardial and pleural effusions are concurrently found after COVID-19 vaccination, vaccine-associated pleuropericarditis should be considered as a differential diagnosis. The aggressive drainage of pericardial and pleural effusions could be helpful not only for diagnosis but also for treatment in the clinical management of COVID-19 vaccine-associated pleuropericarditis. Learning objective: Although the safety and efficacy of BNT162b2 have been widely accepted, it is clinically important to know the potential risk of side effects. When the pericardial and pleural effusions are concurrently found after the vaccination, coronavirus disease 2019 vaccine-associated pleuropericarditis should be considered as a differential diagnosis.